Analysis of Ethico Legal Texts and Abdullah Saeed's Hierarchy of Values in Dealing with Ethico Legal Texts - Ash-Shiddiqy, Muhammad; Diana Fitriyati, Intan (International Proceedings of Nusantara Raya, 2022)
This paper discusses ethico-legal texts and Abdullah Saeed's hierarchy of values ​​in dealing with ethico-legal texts. This paper uses an approach to the literature of the book Interpreting The Qur'an: Towards a Contemporary Approach by Abdullah Saeed. Ethico-legal texts include texts of legal orders, punishments for crimes, belief systems, worship practices, and universal values ​​(kulliyat al khams) such as the maintenance of religion, reason, soul, lineage and property. Interpreting legal-ethical texts according to Abdullah Saeed is a difficult thing because it requires consideration not only of the linguistic aspects of the text but also the socio-historical dimensions. Where the socio-historical interpretation can at the same time reveal the ethical dimensions of the text. The content is often ignored by the commentators and the legal orientation dominates over them. The text or verse is translated directly from the normative-ethical message of the verse. The legal text in the Qur'an is conveyed in detail, except for those relating to verses of worship. To help interpret the ethico-legal text, Saeed formulates what starts with a hierarchy of values ​​which includes obligatory values, fundamental values, protective values, and implementation values. implementation values) and instructional values ​​(instructional values).